2019
DOI: 10.1002/macp.201800460
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin‐Based Films Enhance Rhodamine 6G Emission in the Solid State: A Chemical–Physical Analysis of their Interactions for the Design of Highly Emissive Biomaterials

Abstract: Described herein is the preparation of dye‐doped films employing silk fibroin (SF) as a biomaterial, capable of preserving the optical properties of the monomeric dye in the solid state, a critical requisite for optical and biolaser applications. A comprehensive physical–chemical characterization is reported for SF films doped with Rhodamine 6G, an ideal candidate for photonics and optoelectronics. Fourier transform infrared spectroscopy (FTIR), circular dichroism (CD) and X‐Ray diffraction (XRD) provide infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 58 publications
(102 reference statements)
0
14
0
Order By: Relevance
“…In 2019, Molinari and co-workers reported instead weak ECD signals for transparent films of silk fibroin doped with the achiral rhodamine dye: a negative exciton couplet centered at 546 nm was found, due to the oblique head-to-tail J-dimers of rhodamine molecules originating from the chirality of silk fibroin matrix. 427 Shindo and colleagues casted serious doubts on the authenticity of the induced ECD recorded for the abovedescribed samples, especially the Congo Red 9 in regenerated cellulose swollen films studied by Ritcey and Gray; 425 the simple measurement of ECD spectra at different rotation angles θ around the optical axis does not rule out the existence of contributions different from CD iso . 76,428 For this purpose, they prepared a thin film of the achiral azo-compound Congo Red 9 dispersed in achiral poly(vinyl alcohol) (PVA) and stretched in order to make it macroscopically anisotropic, which surprisingly exhibited intense ECD signals; in particular, if no significant changes in the spectrum were found by sample rotation, 428 a complete inversion of the ECD sign was observed upon sample flipping (Figure 10 in section 2.1.1).…”
Section: Ecd In Thin Films Of π-Conjugated Small Moleculesmentioning
confidence: 99%
“…In 2019, Molinari and co-workers reported instead weak ECD signals for transparent films of silk fibroin doped with the achiral rhodamine dye: a negative exciton couplet centered at 546 nm was found, due to the oblique head-to-tail J-dimers of rhodamine molecules originating from the chirality of silk fibroin matrix. 427 Shindo and colleagues casted serious doubts on the authenticity of the induced ECD recorded for the abovedescribed samples, especially the Congo Red 9 in regenerated cellulose swollen films studied by Ritcey and Gray; 425 the simple measurement of ECD spectra at different rotation angles θ around the optical axis does not rule out the existence of contributions different from CD iso . 76,428 For this purpose, they prepared a thin film of the achiral azo-compound Congo Red 9 dispersed in achiral poly(vinyl alcohol) (PVA) and stretched in order to make it macroscopically anisotropic, which surprisingly exhibited intense ECD signals; in particular, if no significant changes in the spectrum were found by sample rotation, 428 a complete inversion of the ECD sign was observed upon sample flipping (Figure 10 in section 2.1.1).…”
Section: Ecd In Thin Films Of π-Conjugated Small Moleculesmentioning
confidence: 99%
“…Fixing the number of the peaks, their spectral positions and limiting the peak width range, significantly decreases the number of floating parameters and uncertainties. The application of this methodology in FTIR spectral fitting shows consistent results [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 68%
“…A certain restriction was applied in multiple Gaussian component fitting of Amide I bands. The band position and width values associated with various secondary structures were allowed to vary in a fixed range [ 29 , 30 ]. Fixing the number of the peaks, their spectral positions and limiting the peak width range, significantly decreases the number of floating parameters and uncertainties.…”
Section: Methodsmentioning
confidence: 99%
“…Silk cocoons from the silkworm of Bombyx mori were used to obtain silk fibroin using a widely employed degumming procedure [ 24 , 25 ]. Silk cocoons cut into small pieces boiled for 30 min in 0.02 M Na 2 CO 3 (Fisher Sci.)…”
Section: Methodsmentioning
confidence: 99%
“…Aggregate formation of the ligand (rhodamine 6G) in the SF matrix was examined previously. It has been shown that the ligand binding to the protein prevents aggregate formation even in mM concentrations of the ligand [ 25 ]. Besides, the lifetimes of DAS components of ANS fluorescence are not changed much in the films with various SF:ANS ratios.…”
Section: Methodsmentioning
confidence: 99%